Developing a National Research Agenda to Support Healthy Food Retail - Hecht, Amelie A. (Int J Environ Res Public Health, 2020)
The food retail environment is an important driver of dietary choices. This article presents a national agenda for research in food retail, with the goal of identifying policies and corporate practices that effectively promote healthy food and beverage purchases and decrease unhealthy purchases. The research agenda was developed through a multi-step process that included (1) convening a scientific advisory committee; (2) commissioned research; (3) in-person expert convening; (4) thematic analysis of meeting notes and refining research questions; (5) follow-up survey of convening participants; and (6) refining the final research agenda. Public health researchers, advocates, food and beverage retailers, and funders participated in the agenda setting process. A total of 37 research questions grouped into ten priority areas emerged. Five priority areas focus on understanding the current food retail environment and consumer behavior and five focus on assessing implementation and effectiveness of interventions and policies to attain healthier retail. Priority topics include how frequency, duration, and impact of retailer promotion practices differ by community characteristics and how to leverage federal nutrition assistance programs to support healthy eating. To improve feasibility, researchers should explore partnerships with retailers and advocacy groups, identify novel data sources, and use a variety of study designs. This agenda can serve as a guide for researchers, food retailers, funders, government agencies, and advocacy organizations.